Increasing the Gelling Functionality of Lupin Protein Using Ultrasound Treatment - Al-Ali, Hayder A. (Curtin University, 2020)
Protein concentrate from the legume seed lupin has great potential in human nutrition however it use as a food ingredient is limited by its lack of gelling properties. The use of ultrasound to increase the gelling ability of the protein was optimised using statistical modelling and associated molecular changes were identified. The resulting modified protein with strong gelling ability has great potential as a texturising ingredient in a wide range of plant-based foods.